Integrating Academic Press and Support by Increasing Student Ownership and Responsibility - Marisa Ann Cannata; Thomas M. Smith; Katherine Taylor Haynes (SAGE Publishing, 2017)
This article extends existing research on school effectiveness by focusing on identifying the combination of programs, practices, processes, and policies that explain why some high schools in a large urban district are effective at serving low-income students, minority students, and English language learners. Using a mixed methods study of high schools selected on the basis of value-added indicators, we conducted a comparative case study to understand what differentiated schools that "beat the odds" from those that struggled to improve student achievement. We found that the higher-value-added schools enacted practices that integrated academic press and support in ways that fostered student efficacy and engagement. These findings contribute to the larger literature on school effectiveness by highlighting the importance of the student culture of learning and noncognitive student characteristics. They do so by identifying student ownership and responsibility as a critical area for research on school effectiveness and improvement.